Genetic Variability, Correlation and Path Co-Efficient Analysis for Agronomic Traits in Chickpea (Cicer arietinum L.) (The Agriculturists, 2010)
Forty genotypes of chickpea (Cicer arietinum L.) were studied in a field experiment conducted at the experimental field of BARI, Joydebpur, during the year 2004-2005. Significant genetic variations were observed among the genotypes for days to flower, plant height, number of branches per plant, number of pods per plant, 100-seed weight and seed yield per plant. The highest genotypic variability was observed in number of seeds per pod and seed yield, followed by number of pods per plant and branches per plant, whereas days to maturity showed the lowest genotypic co-efficient of variability. In all cases, phenotypic variances were higher than the genotypic ones. High heritability coupled with high genetic advance was observed for seed yield per plant, pods per plant, 100-seed weight and dry weight per plant, which indicates that selection could be effective for these traits. Considerable heritability was observed in pod length, seeds per pod and days to flowering. The results showed that seed yield per plant had positive and significant relation with branches per plant and pods per plant. Number of pods per plant were positively correlated with branches per plant but negatively correlated with plant height and days to first flowering. Weight of 100-seed had significant and positive correlation with days to first flowering, dry weight per plant and pod length but had negative correlation with pods per plant and seeds per pod. Days to first flowering, pod length, pods per plant, dry weight per plant had direct effect on yield. Therefore, days to first flowering, pods per plant, pod length, branches per plant and dry weight per plant are found the important characters which could be used in selection for yield.